2016
DOI: 10.1159/000447255
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Amide Exerts Possible Neuroprotective Effects in Newborn Pigs after Perinatal Asphyxia

Abstract: Background: Perinatal asphyxia and ensuing reoxygenation change the antioxidant capacity of cells and organs. Objectives: To analyze the neuroprotective effect of the antioxidant N-acetylcysteine amide (NACA) after perinatal hypoxia-reoxygenation with an emphasis on proinflammatory cytokines and the transcription factor NF-κB in the prefrontal cortex of neonatal pigs. Methods: Twenty-nine newborn pigs, aged 12-36 h, were subjected to global hypoxia and hypercapnia. One sham-operated group (n = 5) and 2 experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Additional adjuvant strategies There are other treatments that have been tried out in addition to therapeutic hypothermia. These include noble gasses like Xenon and Argon, remote ischemic post-conditioning and the free-radical scavengers N-acetylcystein and N-acetylcystein amide [100][101][102][103][104][105] .…”
Section: Cannabinoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional adjuvant strategies There are other treatments that have been tried out in addition to therapeutic hypothermia. These include noble gasses like Xenon and Argon, remote ischemic post-conditioning and the free-radical scavengers N-acetylcystein and N-acetylcystein amide [100][101][102][103][104][105] .…”
Section: Cannabinoidsmentioning
confidence: 99%
“…This was the first study that we know where DHA was administered in a large-animal model. We wanted to investigate the following in our well established piglet model: Preclinical models of hypoxic-ischemic injury involve a range from invitro studies of cell cultures 154 and brain slices 155 to animal models ranging from rodents 133,138 to larger lamb 156,157 and piglet models 59,89,103 and even to non-human primates 158 .…”
Section: Aims Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has recently described anti-inflammatory and possible neuroprotective effects of the antioxidant N-acetylcysteine amide (NACA) after neonatal hypoxia-reoxygenation in a neonatal pig model. Further, NACA reduced the levels of the proinflammatory cytokine IL-1 β and the transcription factor NF- κ B in the prefrontal cortex of the brain after neonatal hypoxia-reoxygenation [ 6 ]. The substance NACA has many similarities with N-acetylcysteine, which has been used as an antioxidant precursor to glutathione in the treatment of paracetamol overdose for more than 30 years [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have published a study demonstrating that NACA displayed antiinflammatory properties after exposure to oxidative stress in an established neonatal piglet model, imitating perinatal asphyxia [2]. Our piglet model has been established for many years and several authors have shown a significant increase in markers of oxidative stress after the inflicted asphyxia [3].…”
Section: Introductionmentioning
confidence: 97%